The Importance of Collaboration of the Home Health Care Unit and Pediatric Palliative Care Unit in Children - Nilgün Harputluoğlu; Tanju Çelik; Utku Karaarslan; Sevil Uysal (Galenos Yayinevi, 2021)
Introduction:In recent years, advances in technology and medicine have led to an increase in the number of children with chronic diseases, while reducing the mortality rates of pediatric patients. In this study, it was aimed to evaluate the general characteristics and hospitalizations of pediatric patients receiving health care at home from our hospital.Methods:The study was carried out at the University of Health Sciences Turkey, İzmir Dr. Behçet Uz Children's Hospital. The cases registered to the home health services unit between 2012 and 2018 were evaluated retrospectively. The demographic features, diseases, medical devices and technological dependence and hospitalization information of these patients were accessed from the hospital registration system. Data were recorded on SPSS program and evaluated statistically.Results:The average age of 124 patients enrolled in the home health services unit was 8.4 (0.6-17.8) years, and 56.5% were male. 71.8% of the patients were diagnosed with a primary neurological disease, especially cerebral palsy. Tracheostomy was present in 31.5% of the patients and 25% were receiving respiratory support by mechanical ventilation. Gastrotomy was present in 12.9% of the patients. While policlinic applications of those with primary neurological disease were significantly higher (p=0.04) compared to the patient group other than neurological disease, hospitalization rates were similar (p>0.05).Conclusion:The neurological group of patients, including pediatric patients with medical devices and technology dependence, is the main group among the patients who are monitored in the home health care unit. Specialized pediatric palliative care services need to be opened and developed in order to meet the medical, psychological and social needs of these patients and to reduce the workload and occupancy of special units such as intensive care.